Detection of salmonella enteritidis in a immunocompetent patient with myocarditis miyokardit tanılı immünokompetan hastada salmonella enteritidis saptanması - ÖZTÜRK, FATİH EMİN; YILDIZ, YASİN (My University, 2022)
© 2022. Turk Hijyen ve Deneysel Biyoloji Dergisi.All Rights ReservedSalmonella is a gram-negative, motile, non-sporeforming, facultative anaerobic bacterium belonging to the Enterobacteriaceae family. There are several subtypes that can cause disease in humans and animals. Infection can be caused by food, such as eggs, poultry, contaminated waters, and can also be monitored after contact with animals. In humans, it may present with different clinics ranging from asymptomatic carriage to enteric fever. Factors such as the age of the host, immunosuppressive status and additional comorbidities may be effective in the course of the disease. Extraintestinal complications can be observed during the course of enteric fever clinic. Among these complications, clinical conditions such as endocarditis, visceral abscess, osteomyelitis can be considered. In this case, we presented the myocarditis clinic in a patient who presented with vomiting, chest pain and diarrhea, and Salmonella was found in the stool

Salmonella, gram negatif, hareketli, sporsuz, fakültatif anaerobik, Enterobacteriaceae ailesine ait bir bakteri türüdür. İnsanlarda ve hayvanlarda hastalık yapabilen çeşitli alt tipleri mevcuttur. Bulaşma yumurta, kümes hayvanları, kontamine sular gibi gıda kaynaklı olabileceği gibi hayvanlarla temas sonrasında da izlenebilmektedir. İnsanlarda asemptomatik taşıyıcılıktan enterik ateşe kadar farklı kliniklerle ortaya çıkabilir. Hastalığın seyrinde konağın yaşı, immunsupresif durumu ve ek komorbiditeleri gibi faktörler etkili olabilmektedir. Enterik ateş kliniği seyri sırasında extraintestinal komplikasyonlar izlenebilmektedir. Bu komplikasyonlar arasında endokardit, viseral abse, osteomyelit gibi klinik durumlar sayılabilmektedir. Biz de bu vakamızda kusma, göğüs ağrısı ve diyare kliniği ile gelen gaitada Salmonella saptanan hastada myokardit kliniğini sunduk.
Keywords: Tıp; Mikrobiyoloji ve Klinik Mikrobiyoloji; Sosyal ve Beşeri Bilimler; Sosyoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Temel Bilimler; Medicine; Microbiology and Clinical Microbiology; Social Sciences and Humanities; Sociology; Life Sciences; Health Sciences; Fundamental Medical Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Sosyal Bilimler (SOC); İmmünoloji; Mikrobiyoloji; Sosyal Bilimler Genel; BULAŞICI HASTALIKLAR; MİKROBİYOLOJİ; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Life Sciences (LIFE); Social Sciences (SOC); IMMUNOLOGY; MICROBIOLOGY; SOCIAL SCIENCES, GENERAL; INFECTIOUS DISEASES; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; Halk, Çevre ve İş Sağlığı; Mikrobiyoloji (tıbbi); Bulaşıcı hastalıklar; Public Health, Environmental and Occupational Health; Microbiology (medical); Infectious Diseases; Diarrhea; Myocarditis; Salmonella; Miyokardit; Salmonella; diyare